2018
DOI: 10.1177/1073858418793077
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte Bioenergetics in Health and Disease

Abstract: The human brain weighs approximately 2% of the body; however, it consumes about 20% of a person's total energy intake. Cellular bioenergetics in the central nervous system involves a delicate balance between biochemical processes engaged in energy conversion and those responsible for respiration. Neurons have high energy demands, which rely on metabolic coupling with glia, such as with oligodendrocytes and astrocytes. It has been well established that astrocytes recycle and transport glutamine to neurons to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 68 publications
1
59
0
Order By: Relevance
“…Astroglia can supply lactate directly at Ranvier nodes, similar to their actions at tripartite synapses. However, a recent report has elucidated that oligodendroglia metabolize glucose glycolytically to produce lactate . Glucose supplied from microvessels can be used as a direct substrate for oligodendroglia to support neuronal energy metabolism .…”
Section: Summary and Unsolved Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Astroglia can supply lactate directly at Ranvier nodes, similar to their actions at tripartite synapses. However, a recent report has elucidated that oligodendroglia metabolize glucose glycolytically to produce lactate . Glucose supplied from microvessels can be used as a direct substrate for oligodendroglia to support neuronal energy metabolism .…”
Section: Summary and Unsolved Issuesmentioning
confidence: 99%
“…However, a recent report has elucidated that oligodendroglia metabolize glucose glycolytically to produce lactate. 169,170 Glucose supplied from microvessels can be used as a direct substrate for oligodendroglia to support neuronal energy metabolism. 9,171,172 The CMR glc in the white matter is much less than that in the gray matter, and the exact contributions of astroglia, oligodendroglia, and neurons (axons) to CMR glc and the pathways of glucose transport to oligodendroglia and neurons remain to be solved.…”
Section: Compartmentalization Between Oligodendroglia and Astrogliamentioning
confidence: 99%
“…Limited remyelination occurs in multiple sclerosis (MS) lesions despite the presence of OPCs in or around lesion sites. These OPCs exhibit markers of metabolic stress, and, while capable of initiating a remyelination program, fail to do so (6).…”
Section: Introductionmentioning
confidence: 99%
“…Markers of aging and senescence have also been reportedly localized to oligodendroglia in normal aging [163,167] and in age-related neurodegenerative diseases [138,164,168]. These changes have been implicated to have a significant pathogenic role in diseases, including MS, Alzheimer's Disease (AD), dementia, and amyotrophic lateral sclerosis (ALS) [2,163,164,169]. In ALS, a recent study has shown an energetic dysfunction in oligodendrocyte-axonal coupling and failure of new oligodendrocytes to mature, resulting in demyelination [170].…”
Section: Effect Of Agingmentioning
confidence: 99%
“…Myelin is crucial for saltatory propagation of electrical impulses down the axon, enabling rapid communication between networks of neurons in the CNS [1]. In addition to increasing axonal conduction speed through generating myelin, OLs secrete metabolic factors and maintain energy homeostasis to support axonal integrity and promote neuronal survival [2]. Thus, establishing proper numbers of OLs during brain development, as well as during their regeneration in neurological disorders that involve OL and myelin loss, is crucial for normal CNS function.…”
Section: Introductionmentioning
confidence: 99%